Depressive symptoms in relation to overall survival in people with head and neck cancer: A longitudinal cohort study. Issue 9 (23rd July 2018) - Jansen, Femke; Verdonck‐de Leeuw, Irma M.; Cuijpers, Pim; Leemans, C. René; Waterboer, Tim; Pawlita, Michael; Penfold, Chris; Thomas, Steven J.; Waylen, Andrea; Ness, Andrew R.
Abstract: Objective: The objective of the study is to investigate the relation between pretreatment depressive symptoms (DS) and the course of DS during the first year after cancer diagnosis, and overall survival among people with head and neck cancer (HNC). Methods: Data from the Head and Neck 5000 prospective clinical cohort study were used. Depressive symptoms were measured using the Hospital Anxiety and Depression Scale (HADS) pretreatment, at 4 and 12‐month follow‐up. Also, socio‐demographic, clinical, lifestyle, and mortality data were collected. The association between before start of treatment DS (HADS‐depression > 7) and course (never DS, recovered from DS, or persistent/recurrent/late DS at 12‐month follow‐up) and survival was investigated using Cox regression. Unadjusted and adjusted analyses were performed. Results: In total, 384 of the 2144 persons (18%) reported pretreatment DS. Regarding DS course, 63% never had DS, 16% recovered, and 20% had persistent/recurrent/late DS. People with pretreatment DS had a higher risk of earlier death than people without DS (hazard ratio (HR) = 1.65; 95% confidence interval (CI) 1.33‐2.05), but this decreased after correcting for socio‐demographic, clinical, and lifestyle‐related factors (HR = 1.21; 95% CI 0.97‐1.52). Regarding the course of DS, people with persistent/recurrent/late DS had a higher risk of earlier death (HR = 2.04; 95% CI 1.36‐3.05), while people who recovered had a comparable risk (HR = 1.12; 95% CI 0.66‐1.90) as the reference group who never experienced DS. After correcting for socio‐demographic and clinical factors, people with persistent/recurrent/late DS still had a higher risk of earlier death (HR = 1.66; 95% CI 1.09‐2.53). Conclusions: Pretreatment DS and persistent/recurrent/late DS were associated with worse survival among people with HNC.